Krisis Ekologi dan Etika Ekologis dalam Novel Teruslah Bodoh Jangan Pintar Karya Tere Liye - Wahyudin, Syabrina; Wiyatmi, Wiyatmi; Efendi, Anwar (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
The escalation of the ecological crisis caused by massive extractive industrial activities necessitates the strengthening of environmental literacy through cultural media. This study aims to explore the representation of the ecological crisis and the dynamics of ecological ethics in Tere Liye’s novel Teruslah Bodoh Jangan Pintar using Greg Garrard’s ecocritical perspective. The research method employed is descriptive qualitative with content analysis techniques. The results indicate that the novel reconstructs the ecological crisis based on the three primary pillars of Greg Garrard's ecocriticism, namely: pollution as structural violence, dwelling as landscape alienation, and local apocalypse as a consequence of reclamation failure. These findings reveal a dialectic in the community's ecological ethics, shifting from a passive stance to a reactive collective advocacy movement in response to environmental repression. The novelty of this research lies in its focus on contemporary popular literature that deconstructs the conflicts of the modern mining industry, while affirming the role of popular novels as effective instruments for socio-ecological critique in Indonesia.